LAMP-on-a-chip: Revising microfluidic platforms for loop-mediated DNA amplification - Zhang, Haoqing; Xu, Ying; Fohlerova, Zdenka; Chang, Honglong; Iliescu, Ciprian; Neuzil, Pavel (Trends in analytical chemistry, 2019)
Nucleic acid amplification for the detection of infectious diseases, food pathogens, or assessment of genetic disorders require a laboratory setting with specialized equipment and technical expertise. Isothermal deoxyribonucleic acid amplification methods, such as loop-mediated isothermal amplification (LAMP), exhibit characteristics ideal for point-of-care (POC) applications, since their instrumentation is simpler in comparison with the standard method of polymerase chain reaction. Other key advantages of LAMP are robustness and the production of pyrophosphate in the presence of the target gene, enabling to detect the reaction products using the naked eye. Polymerase inhibitors, presented in clinical samples, do not affect the amplification process, making LAMP suitable for a simple sample-to-answer diagnostic systems with simplified sample preparation. In this review, we discuss the trends in miniaturized LAMP techniques, such as microfluidic, paper-based, and digital with their advantages and disadvantages, especially for POC applications alongside our opinion of the future development of miniaturized LAMP.
Keywords: LAMP; Multi gene detection; Digital LAMP; POC; Paper-based LAMP; Single gene detection; Microfluidic; PCR